Natural vs. surgical postmenopause and psychological symptoms confound the effect of menopause on executive functioning domains of cognitive experience. (April 2023) - Page, Chloe E.; Soreth, Brianna; Metcalf, Christina A.; Johnson, Rachel L.; Duffy, Korrina A.; Sammel, Mary D.; Loughead, James; Epperson, C. Neill
Highlights: Compared with premenopausal women, perimenopausal and surgical postmenopausal women experience more perceived executive dysfunction. Problems with perceived executive dysfunction were significantly higher in natural postmenopausal than in premenopausal women without controlling for difficulty sleeping, anxiety, and depression, but not when adjusting for these variables. Menopause type (natural vs. surgical) and psychological symptoms (sleep, anxiety, and depression) are important confounders of the relationship between menopause and perceived executive function. Abstract: Objective: The menopause transition is associated with difficulties in executive function. However, it is unclear whether these difficulties persist past perimenopause. This study investigated whether potential confounders, including natural vs. surgical postmenopause and menopause-related psychological symptoms, influence whether executive dysfunction persists into postmenopause. Study design: A cross-sectional sample of women aged 35–65 years (N = 1971) in one of four groups, premenopause, perimenopause, natural postmenopause, and surgical postmenopause, were surveyed. Participants self-reported executive functioning with the Brown Attention Deficit Disorder Scale (BADDS), anxiety symptom severity with the Generalized Anxiety Disorder Questionnaire (GAD-7), and depression symptom severity with the Center for Epidemiologic Studies Depression Scale (CESD). Main outcome measures: We analyzed the association between group and BADDS scores using linear regression models – first, by controlling for age, education, and self-reported attention deficit hyperactivity disorder (ADHD) diagnosis (Model #1) and, second, by further controlling for current difficulty sleeping, anxiety, and depression (Model #2). Results: In both models, BADDS scores were significantly elevated (indicating more difficulties in executive function) among women in the perimenopausal and surgical postmenopausal groups compared with those in the premenopausal group. Likewise, the perimenopausal and surgical postmenopausal groups had the highest proportions of participants who reported difficulty sleeping and clinical levels of anxiety and depression. BADDS scores were significantly higher in natural postmenopausal vs. premenopausal women without controlling for difficulty sleeping, anxiety, and depression (Model #1), but not when adjusting for these variables (Model #2). Conclusions: The type of menopause and psychological symptoms are important confounders of the relationship between the menopause transition and executive dysfunction, and help explain whether executive dysfunction persists or recovers in postmenopause.